2015
DOI: 10.1002/bmb.20852
|View full text |Cite
|
Sign up to set email alerts
|

Using HeLa cell stress response to introduce first year students to the scientific method, laboratory techniques, primary literature, and scientific writing

Abstract: Incorporating scientific literacy into inquiry driven research is one of the most effective mechanisms for developing an undergraduate student's strength in writing. Additionally, discovery-based laboratories help develop students who approach science as critical thinkers. Thus, a three-week laboratory module for an introductory cell and molecular biology course that couples inquiry-based experimental design with extensive scientific writing was designed at Westminster College to expose first year students to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Perturbation of HeLa (i.e., human fibroblast cells) and broad monitoring of the cells' proteome by SDS-polyacrylamide electrophoresis was done with a single, class-chosen environmental stimulus [20]. Perturbation of HeLa (i.e., human fibroblast cells) and broad monitoring of the cells' proteome by SDS-polyacrylamide electrophoresis was done with a single, class-chosen environmental stimulus [20].…”
Section: Resultsmentioning
confidence: 99%
“…Perturbation of HeLa (i.e., human fibroblast cells) and broad monitoring of the cells' proteome by SDS-polyacrylamide electrophoresis was done with a single, class-chosen environmental stimulus [20]. Perturbation of HeLa (i.e., human fibroblast cells) and broad monitoring of the cells' proteome by SDS-polyacrylamide electrophoresis was done with a single, class-chosen environmental stimulus [20].…”
Section: Resultsmentioning
confidence: 99%
“…All the students have biology as one of the subjects in their first year in their colleges. Going through the literature cited earlier, we found that a few of the papers involved first‐year undergraduates. Encouraged by their results and constrained by the circumstances indicated previously, we decided to carry out a short 3‐day intervention on the sample of 29 first‐year students who visited our institution in 2018.…”
Section: Introductionmentioning
confidence: 93%
“…Yet, elsewhere in the world, science teachers and educators have successfully designed different approaches to include research paper reading in undergraduate courses . One of the most serious efforts in this connection that we have come across is “CREATE.” In this approach, students read four consecutive publications (from the same biology research laboratory) over the course of a semester .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Lerner (2007) traces interest in the teaching of this genre dating from at least 1890. This interest continues and the laboratory’s teaching and learning processes are an object of study in the scientific education of multiple disciplines, mostly due to the impact that both the traditional method and more recent inquiry-based ( Resendes, 2015 ) and virtual simulation approaches ( Rodríguez-Llerena and Llovera-González, 2014 ) have on learning.…”
Section: Introductionmentioning
confidence: 99%